비탈면 안정을 위한 참싸리 뿌리의 토양보강 효과 - 황진성; 지병윤; 오재헌; 차두송 (Journal of forest and environmental science , 30(1), 2014)
To examine the soil reinforcement by the shrub with shallow root systems for slope stability, we developed insitu apparatus for direct shear test and conducted the insitu field tests for Lespedeza cyrtobotrya, a representative revegetation species for artificial hillslopes. The insitu field tests were conducted for two different soil conditions (the rooted soils and non-rooted soils) and we then compared the experimental values with those calculated from the Wu model. The results showed that the soil reinforcement derived from the insitu field tests ranged from 0.01525 to 0.1438 kgf/cm² while the one calculated from the Wu model ranged from 0.1952 to 0.2696 kgf/cm² . Our finding suggests more field tests are needed to collect the related parameters in the model application thereby predicting the reliable soil reinforcement by the shrub root systems. KCI Citation Count: 0